An investigation into entrepreneurial intentions in Caribbean Small Island Developing States - Preeya Mohan (Journal of Innovation and Entrepreneurship, 2022)
This paper explored entrepreneurial intentions in the Caribbean adult population using a social cognitive approach. It used the Global Entrepreneurship Monitor (GEM) Adult Population Survey (APS), which includes questions about entrepreneurial intentions of potential business owners and entrepreneurial perceptions, namely individual, entrepreneurial opportunities and socio-cultural, along with demographic and socio-economic variables. The effect of perceptions along with socio-economic control variables on entrepreneurial intentions was investigated using probit regression models. The results confirm that even after controlling for demographic and socio-economic and country fixed effects, social cognitive perceptions were indeed relevant in explaining entrepreneurial intentions in the region. This study therefore provides insights into understanding entrepreneurship in particular the decision to form a new business through the individual's perceptions and intentions.
Keywords: 650; Cognitive models; Entrepreneurial intention; Entrepreneurship; Probit models; Small Island Developing States